Analysis of Lecturer Performance in the Application of The Online Learning Process - Novi Hendri Adi; Afif Rahman Riyanda; Margaretha Karolina Sagala; Ambiyar Ambiyar; Syaiful Islami; Mahesi Agni Zaus (JTEV (Jurnal Teknik Elektro dan Vokasional), 2022)
The reason for this paper is to acquire execution data from the application of online learning from 3 aspects, in particular: planning learning, implementing learning, and evaluating learning using a quantitative technique approach. he sample in this study was 30 lecturers of Technical and Vocational Education and Training (TVET). The outcomes showed that: (1) the learning planning obtained was 82.26% classified as good category; (2) carry out learning with a percentage of 78.96% belonging to the fairly good category; (3) online learning obtained by 79.13 percent is quite good. The overall results obtained are 80.12 percent which shows the performance of lecturers in the application of learning in the category of being brave and good.